Ageing and longevity in the Decapoda (Crustacea): a review - Vogt, Günter (Zoologischer Anzeiger, 2012)
Ageing and longevity is a neglected field of crustacean biology. Information on longevity is available for less than 2% of the extant species of the Decapoda. Maximum ages reliably determined range from 40 days to 72 years corresponding to a life span difference of a factor of 650. The shortest-lived decapods are planktonic dendrobranchiate shrimps, and particularly long-lived species with life spans of decades are found in the Astacidea. Most decapods seem to live for 1-10 years. High geographical latitude, the deep sea and freshwater caves promote longevity. The majority of the Decapoda is indeterminately growing and presumably characterized by negligible senescence. The adults of the determinately growing decapods like some brachyuran crabs suffer from mechanical senescence and are unable to regenerate lost appendages. The decapod crustaceans have developed many effective anti-ageing mechanisms including moulting, detoxification of free radicals, removal of cellular waste, renewal of tissues by life-long stem cell activity, regeneration of appendages, detoxification of environmental pollutants and isolation of pathogens and diseased tissue areas by melanisation and encapsulation. Age related diseases including cancer are virtually unknown. The present compilation of data on longevity and senescence in decapods is the first one that covers the whole spectrum of a higher invertebrate taxon. It is hoped to provide an interesting source of information for carcinologists and biogerontologists. Further improvement of knowledge on ageing and longevity in the Decapoda would be beneficial for crustacean aquaculture, fisheries and ecological modelling. Some decapods even have good potential to become models for general ageing research.
Gesehen am 08.10.2018